INCITE : the magazine for library and information professionals. (Deakin, ACT : Australian Library and Information Association., 2012)
Incite is the premier magazine for the library and information sector in Australia and it presents perspectives on issues relating to library and information science.
Also available in print.
Keywords: Libraries -- Periodicals; Libraries -- Australia -- Periodicals; Australian